On the Asymptotics of Some Weierstrass Functions - Zaionts, Yu.; Korenkov, M. E.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
For Weierstrass functions σ(z) and ζ(z), we present the asymptotic formulas valid outside the efficiently constructed exceptional sets of discs that are much narrower than in the known asymptotic formulas.